Acute performance, daily well-being, and hormone responses to water immersion after resistance exercise in junior international and subelite male volleyball athletes - Horgan, B. G.; Tee, N.; West, N. P.; Drinkwater, E. J.; Halson, S. L.; Colomer, C. M. E.; Fonda, C. J.; Tatham, J.; Chapman, D. W.; Haff, G. G. (The Journal of Strength and Conditioning Research, 2023)
Athletes use postexercise hydrotherapy strategies to improve recovery and competition performance and to enhance adaptative responses to training. Using a randomized cross-over design, the acute effects of 3 postresistance exercise water immersion strategies on perceived recovery, neuromuscular performance, and hormone concentrations in junior international and subelite male volleyball athletes (n = 18) were investigated. After resistance exercise, subjects randomly completed either 15-minute passive control (CON), contrast water therapy (CWT), cold (CWI), or hot water immersion (HWI) interventions. A treatment effect occurred after HWI; reducing perceptions of fatigue (HWI > CWT: p = 0.05, g = 0.43); improved sleep quality, compared with CON (p < 0.001, g = 1.15), CWI (p = 0.017, g = 0.70), and CWT (p = 0.018, g = 0.51); as well as increasing testosterone concentration (HWI > CWT: p = 0.038, g = 0.24). There were trivial to small (p < 0.001-0.039, g = 0.02-0.34) improvements (treatment effect) in jump performance (i.e., squat jump and countermovement jump) after all water immersion strategies, as compared with CON, with high variability in the individual responses. There were no significant differences (interaction effect, p > 0.05) observed between the water immersion intervention strategies and CON in performance (p = 0.153-0.99), hormone (p = 0.207-0.938), nor perceptual (p = 0.368-0.955) measures. To optimize recovery and performance responses, e.g., during an in-season competition phase, postresistance exercise HWI may assist with providing small-to-large improvements for up to 38 hours in perceived recovery (i.e., increased sleep quality and reduced fatigue) and increases in circulating testosterone concentration. Practitioners should consider individual athlete neuromuscular performance responses when prescribing postexercise hydrotherapy. These findings apply to athletes who aim to improve their recovery status, where postresistance exercise HWI optimizes sleep quality and next-day perceptions of fatigue.